Comparative Study on Supercapacitive Performances of Hierarchically Nanoporous Carbon Materials With Morphologies From Submicrosphere to Hexagonal Microprism - Xie, Lei; Yuan, Kai; Xu, Jianxiong; Zhu, Yirong; Xu, Lijian; Li, Na; Du, Jingjing (Frontiers in Chemistry, 2020)
Hierarchically nanoporous carbon materials (HNCMs) with well-defined morphology and excellent electrochemical properties are promising in fabrication of energy storage devices. In this work, we made a comparative study on the supercapacitive performances of HNCMs with different morphologies. To this end, four types of HNCMs with well-defined morphologies including submicrospheres (HNCMs-S), hexagonal nanoplates (HNCMs-N), dumbbell-like particles (HNCMs-D) and hexagonal microprisms (HNCMs-P) were successfully synthesized by dual template strategy. The relationship of structural-electrochemical property was revealed by comparing the electrochemical performances of these HNCMs based electrodes using a three-electrode system. The results demonstrated that the HNCMs-S based electrode exhibited the highest specific capacitance of 233.8 F g-1 at the current density of 1 A g-1 due to the large surface area and well-defined hierarchically nanoporous structure. Moreover, the as-prepared HNCMs were further fabricated into symmetrical supercapacitor devices (HNCMs-X//HNCMs-X) using KOH as the electrolyte and their supercapacitive performances were checked. Notably, the assembled HNCMs-S//HNCMs-S symmetric supercapacitors displayed superior supercapacitive performances including high specific capacitance of 55.5 F g-1 at 0.5 A g-1, good rate capability (retained 71.9% even at 20 A g-1), high energy density of 7.7 Wh kg-1 at a power density of 250 W kg-1 and excellent cycle stability after 10000 cycles at 1 A g-1. These results further revealed the promising prospects of the prepared HNCMs-S for high performances energy storage devices.